Ocorrência de Lymnaea columella (Gastropoda: Lymnaeidae), hospedeiro intermediário da Fasciola hepatica, para o Estado da Paraíba, Brasil Occurrence of Lymnaea columella (Gastropoda: Lymnaeidae), first intermediate host of Fasciola hepatica, for the state of Paraíba, Brazil - Francisco José Pegado Abílio; Takako Watanabe (Universidade de São Paulo, 1998)
Foi registrada a ocorrência de Lymnaea columella (Gastropoda: Lymnaeidae), primeiro hospedeiro intermediário da Fasciola hepatica, para o Estado da Paraíba, Brasil, associado a macrófitas aquáticas. The occurrence of Lymnaea Columella (Gastropoda: Lymnaeidae), first intermediate host of Fasciola hepatica, is recorded for the first time in the state of Paraíba, Brazil, associeted with aquatic macrophytes.